2013
DOI: 10.1155/2013/319073
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Antidepressive Effects of aWakan-yaku,Hochuekkito, in Depression Model Mice with Learned-Helplessness Behavior

Abstract: Wakan-yaku is a type of Japanese and Sino traditional, systematized medical care that has been practiced for hundreds of years. This medicinal system includes many antidepressive prescriptions. One of the candidates is Hochuekkito, although experimental evidence has not yet been established clearly. To obtain evidence, a depression model of learned-helplessness (LH) mice was used. Based on the score of escape failure, an index of the depression degree, mice with a depressive condition were selected to assess H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…It was reported that large numbers of patients with COPD had clinically significant levels of depression and/or anxiety ( 28 , 29 ). Tohda and Mingmalairak ( 30 ) reported that TJ-41 had an antidepressive effect in a mouse model of depression with learned helplessness behavior. Further study is needed to clarify the antidepressive effect of TJ-41 in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that large numbers of patients with COPD had clinically significant levels of depression and/or anxiety ( 28 , 29 ). Tohda and Mingmalairak ( 30 ) reported that TJ-41 had an antidepressive effect in a mouse model of depression with learned helplessness behavior. Further study is needed to clarify the antidepressive effect of TJ-41 in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of the first reports on the influence of a potential alternative medicine is fundamental to establish good medicine practices. The previous reports relating the influence of alternative medicines over behavior have been done, such as to honey,[ 22 ] to the sino-japanese wakan-yaku,[ 23 ] to uncaria hook[ 24 ] and others. [ 25 26 ] Lupeol, β-amyrin and 3 β-hydroxyglutin-5-ene were previously isolated from S. globulifera ,[ 21 ] and molecules were described to occur in the species for the first time, then.…”
Section: Discussionmentioning
confidence: 99%
“…I and co-workers has been reported that HET has antidepressantlike effects in learned helplessness test in mice [1]. We also found that HET is involved serotonin 2C receptor (5-HT2CR) function and the mRNA expression [2] as well as antidepressants [2][3][4].…”
Section: Introductionmentioning
confidence: 90%